2009
DOI: 10.1029/2009gl041438
|View full text |Cite
|
Sign up to set email alerts
|

Self‐focused radio frequency L wave pumping of localized upper hybrid oscillations in high‐latitude ionospheric plasma

Abstract: [1] In experiments on radio frequency pumping of ionospheric plasma it is usually assumed that the pump wave propagates in the ordinary (O) mode. However, it is shown by ray tracing that commonly excited filamentary density inhomogeneities will guide a transmitted O-mode pump wave along the geomagnetic field as an L wave. Nonlinearly guided L-wave pumping of long predicted localized upper hybrid oscillations offers a unified understanding of a range of experimental results, including strong self-focusing for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 18 publications
2
23
2
Order By: Relevance
“…One reason to expect high altitude fields to play an important role is the fact that the zeroth order (and hence uppermost) resonance for UH generation inside a striation gives the largest contribution, as explained by Mjølhus (1998). But we have also seen how ducts help the wave field stay perpendicularly polarised, which in turn facilitates the excitation of UH waves (Leyser and Nordblad, 2009). On top of this, focussing effects are in play, producing regions of intense fields e.g.…”
Section: E Nordblad and T B Leyser: L Mode Pumping Of The Ionospherementioning
confidence: 96%
See 2 more Smart Citations
“…One reason to expect high altitude fields to play an important role is the fact that the zeroth order (and hence uppermost) resonance for UH generation inside a striation gives the largest contribution, as explained by Mjølhus (1998). But we have also seen how ducts help the wave field stay perpendicularly polarised, which in turn facilitates the excitation of UH waves (Leyser and Nordblad, 2009). On top of this, focussing effects are in play, producing regions of intense fields e.g.…”
Section: E Nordblad and T B Leyser: L Mode Pumping Of The Ionospherementioning
confidence: 96%
“…Such effects were reported by Kosch et al (2004), who observed an annular optical structure extending above the reflection height shortly after the onset of pumping. While at a later stage, the emissions collapsed into a blob at lower altitude and were attributed to Langmuir turbulence, this initial annulus could be due to upper hybrid (UH) waves trapped inside small scale density striations, as we argued in Leyser and Nordblad (2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Depending on the plasma density profile, upward propagation into denser plasma continues until either the ray is refracted downward, the Z mode reflection altitude is reached (i.e., X = 1 + Y), or until the plasma density decreases again (discussed below, see equation (6)) and the topside is reached (i.e., X = 1). The Z mode reflection altitude can be approximated by [e.g., Leyser and Nordblad, 2009]:…”
Section: Introductionmentioning
confidence: 99%
“…At high latitudes, optical emissions show self-organization into filaments of a few kilometers across during pumping in at magnetic zenith (Kosch et al, 2007;Leyser and Nordblad, 2009).…”
Section: Introductionmentioning
confidence: 99%